The challenge methodology. A case study to enhance digital competences for teachers - De Angelis, Maria Chiara (Community Notebook. People, Education and Welfare in the Society 5.0, 2021)
The essay shows a reflection about a wider case study aimed to enhance digital skills for teachers. The training model was designed on the basis of the results of the analysis of training needs that was carried out within the DECODE project. Among its activities, this project included the distribution of an online questionnaire, involving more than 2000 teachers from Italy, Spain, Romania, Finland, and the United Kingdom. The purpose of the online training path taken into account in this essay was to guide teachers in the process of empowerment of digital skills, by focusing on the methodological and relational dimension, considered strategic in the learning-teaching processes. Through a Moodle environment has been built a space for discussion and work based on teaching practice, with the aim of increasing digital competences, share best practices and promote a reflexive space of discussion.